La declaración jurada informativa reporte local de precios de transferencia y su contribución como mecanismo de planificación fiscal para combatir la elusión y evasión tributaria - Lozano González, Linda Joshelin (2018)
In the present work the contribution of the Informative Sworn Statement has been investigated and evaluated. Local report for the companies that carry out the activities with the related companies, the benefit of the Tax administration has been analyzed and that this New Report is available. the account a fiscal planning mechanism because with it would increase tax revenues based on a greater collection for the State. The population is made up of 2500 Companies forced to present the Local Report Informative Sworn Statement. According to data extracted from the GESTIÓN 2018 DIARY "Transfer Prices: 2500 Companies declared the Local Report". An integral case has been developed (Total Registry - Informative Sworn Statement, Local Report), which includes the same structure for the 94 companies selected as a sample, due to the fact that their income accrued in 2016 was greater than 2300 Tax Units and their operations with its related companies exceeded 400 Taxation Units. The research was developed using the "Descriptive" and not "Experimental" design. In the same way, the techniques used were bibliographic revision, database revision, documentary analysis, tabulation of data, etc. The results obtained as a result of the research carried out were the following: the evolution was shown and the New Local Report Information Report was analyzed based on the rules on transfer pricing, then it was identified and analyzed the changes that have occurred between the New Report and the Technical Study of Transfer Prices, showing the changes arising in its structure and content, analyzing the benefit that the Peruvian State would have as it would increase its tax collection.